PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. INTER DIGITAL SOLUTIONS - Alfa Fadhila; Isep Amas Priatna (Journal of Research and Publication Innovation, 2025)
This research, titled "The Influence of Work Environment and Work Discipline on Employee Performance at CV. Inter Digital Solutions," aims to analyze the impact of these two factors on employee performance, both individually and collectively. Conducted in West Jakarta, the research employed a quantitative associative method, gathering data through observations and questionnaires completed by 71 respondents using a saturated sampling technique. Data analysis utilized simple and multiple regression tests alongside hypothesis testing. The findings reveal that the work environment significantly affects employee performance (t-value = 4.762, significance = 0.000), as does work discipline (t-value = 5.986, significance = 0.000). Simultaneously, these factors exhibit a combined significant influence (F-value = 42.630, significance = 0.000). The coefficient of determination indicates that the work environment accounts for 49.2% of the variance in employee performance, work discipline for 55.6%, and both variables together for 74.7%, with the remainder attributed to external factors. The research concludes that a conducive work environment and strong work discipline significantly enhance employee performance at CV. Inter Digital Solutions